The talented Miss Farwell : a novel - Tedrowe, Emily Gray (Custom House, 2020)
At the end of the 1990s, with the art market finally recovered from its disastrous collapse, Miss Rebecca Farwell has made a killing at Christie's in New York City, selling a portion of her extraordinary art collection for a rumored 900 percent profit. Dressed in couture YSL, drinking the finest champagne at trendy Balthazar, Reba, as she's known, is the picture of a wealthy art collector. To some, the elusive Miss Farwell is a shark with outstanding business acumen. To others, she's a heartless capitalist whose only interest in art is how much she can make. But a thousand miles from the Big Apple, in the small town of Pierson, Illinois, Miss Farwell is someone else entirely, a quiet single woman known as Becky who still lives in her family's farmhouse, wears sensible shoes, and works tirelessly as the town's treasurer and controller.